Determination of skin wound age by using cytokines as potential markers - TURAN YURTSEVER, NURŞEN (ELSEVIER SCI LTD, 2016)
Interleukin-1 beta ( IL-1 beta), IL-6, tumour necrosis factor-alpha (TNF-alpha) and epidermal growth factor (EGF) play important roles in the wound healing process. In the present study, human wound specimens (n = 50) were collected from cases of death due to injuries from firearms, penetrating trauma by sharp objects and blunt trauma with a known time of injury and death identified by forensic autopsy. Full-thickness tissue specimens were obtained from injured skin sites, and equally sized intact tissues obtained from the same person were used as controls. Protein determination was performed using ELISA according to the Bradford method for each specimen, and results were provided for individual proteins. IL-1 beta levels did not reach statistical significance in any of the wound groups and were not markedly higher than those in the control group. However, IL-6 showed a biphasic pattern and reached statistical significance in the group with wounds less than 30 min old and in the group with wounds more than 18 h old. IL-6 was consistently higher in all wound groups than in the control group. TNF-alpha showed a statistically significant increase within the first 30 min and remained at a high level in all groups except for those with wounds 2-4 h old. On the other hand, EGF was high in all groups excluding those with wounds 2-4 h old and more than 18 h old, but statistical significance was not reached. Our results suggest that IL-6 and TNF-alpha in particular may be used as early-phase markers. We believe that IL-1b and EGF should be more extensively evaluated in further studies. (C) 2016 Elsevier Ltd and Faculty of Forensic and Legal Medicine. All rights reserved.
Keywords: IL-1 beta; IL-6; TNF-alpha; EGF; Wound age; Autopsy; EPIDERMAL-GROWTH-FACTOR; IMMUNOHISTOCHEMICAL DETECTION; PROINFLAMMATORY CYTOKINES; HEALING-PROCESS; ESSENTIAL INVOLVEMENT; TEMPORAL EXPRESSION; INTERFERON-GAMMA; MESSENGER-RNA; TNF-ALPHA; VITALITY